Estudo dos constituintes químicos de óleos voláteis de plantas medicinais do Rio Grande do Sul: isolamento, determinação e modificação estrutural e atividade biológica - Simionatto, Euclésio (2004)
The essential oils of eight species of medicinal plants wild and cultivated in Rio Grande do Sul, pertaining to four botany family Asteraceae, Verbenaceae, Lamiaceae and Rutaceae were investigated as for its chemical composition and antibacterial activity. The selected species for this study were Baccharis trimera and Baccharis articulata (Asteraceae), Matricaria chamomilla (Asteraceae), Pluchea quitoc (Asteraceae), Aloysia sellowii (Verbenaceae), Aeollanthus suaveolens (Lamiaceae), Cunila microcephala (Lamiaceae) and Zanthoxylum hyemale (Rutaceae). The species mentioned were selected for this study by to present extensive use in local medicine as remedy. In this work, the essential oil of each specie were submitted to chromatographic procedures with to aim to isolate its constituents in pure form. The structural analysis of isolated components were realized through chiral and achiral chromatographic technics, reinforcement with standards, obtainment of Kovat s indices, GC-MS and RMN of 1H and 13C uni- and bi dimensional. So that, were possible to identify a inedited sesquiterpene of essential oil from Zanthoxilum hyemale denominated in this work as hyemalol. From essential oil of Calea clematidea were isolated its principal constituent, the natural epoxid caleol, which by abundance and multifunctional structure, were submitted to structural transformations with purpose to realize a study structure-biologic activity. Moreover, the components of volatile oils of propolis from different regions of Rio Grande do Sul, were also analyzed by GC and Chiral-GC. As essential oil on the contrary of others secondary compounds, are constituted by chiral substances in its two enantiomeric form, because this, the present work have as aim, the chiral analysis of this components. For this, were used new stationary phases derived from ciclodextrins, obtained by NPPN group. In conclusion, the essential oil obtained as well as, the isolated components through chromatographic methods were submitted to antibacterial and antifungical tests, using the microdiluition and bioautography methods, through which is possible to observe that the essential oils were active against a greater number of microorganisms.